PEMANFAATAN YOUTUBE SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA KOMPETENSI MENYIMAK CERITA ANAK PADA SISWA KELAS V SEKOLAH DASAR - Naidah, Naidah; Abbas, Asriani; Kaharuddin, Kaharuddin (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The purpose of this study was to improve the learning outcomes of Indonesian language students in class V at SD Negeri Caturtunggal I Depok, Yogyakarta Special Region in the competency of listening to children's stories by utilizing YouTube media. This study used the CAR class action research method. The subjects in this study were fifth grade students at SD Negeri Caturtunggal I Depok, Special Region of Yogyakarta. Data were collected by observation, tests, and interviews. Data were analyzed with an interactive analysis model including reduction, presentation, and drawing conclusions. The research results prove that; 1) there is a change in lesson planning, from conventional learning to modified learning designed by researchers by applying YouTube media in learning. This can be seen from the learning in pre-action, cycle I and cycle II. 2) There is a change in the implementation aspect of the learning action. All forms of learning problems faced by teachers have been corrected so that the learning process can run well. In other words, the application of YouTube media in learning Indonesian for the material "Listen to Children's Stories" can improve the quality of the learning process. 3) The application of YouTube media in Indonesian language learning material "Listen to Children's Stories" can improve student learning outcomes. The increase in learning outcomes was marked by an increase in the number of students who reached the limits of completeness from pre-action, cycle I, to cycle II.